PENERAPAN MODEL PEMBELAJARAN TEMATIK UNT U K MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARA AKIDAH AKHLAK KELAS VIII 2 DI MTS AS’ADIYAH NO.3 ATAPANGE KAB UPATENWAJO - Andi Mulyadi; Akhmad Syahid; M Akil; Andi Bunyamin; Syarifa Raehana; Rosmiati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Andi Mulyadi, This thesis discusses "The Application of the Thematic Learning Model to Improve Student Learning Outcomes in the Class VIII 2 Moral Creed Subject at MTs As'Adiayah Wajo Regency" This research aims to improve the learning outcomes of class VIII 2 students in the Moral Creed Subject by using Thematic learning model and to find out how to apply the thematic learning model in improving Aqidah Akhlak learning outcomes. The method used in this research is Classroom Action Research (PTK). In this research, the research subjects were class VIII 2 students at MTs As'Adiayah, Wajo Regency with a total of 30 students. The instrument used is observation, namely making direct observations of class VIII 2 students at MTs As'Adiyah Wajo Regency, interviews will be carried out by asking several questions to teachers in the Aqidah Akhlak field of study, and tests in the form of initial tests and final tests in the form of multiple choices. 10 questions. The results of the research that has been carried out show that student learning outcomes have increased. This increase can be seen through the cycles that have been carried out, where in the pre-cycle the average score of students was 63 (fair) with a completion percentage of 40%, then in cycle I the average score was 72.5 (good) with a completion percentage of 66. 66%, in cycle II the average score was 82.83 very good) with a completion percentage of 83.33%.